A Proposal for Sharing Software Process Provenance Data in Heterogeneous Environments - Costa, Gabriella; Teixeira, Eldânae Nogueira; Werner, Cláudia; Braga, Regina (Anais do Workshop de Práticas de Ciência Aberta para Engenharia de Software (OpenScienSE); 2021: Anais do I Workshop de Práticas de Ciência Aberta para Engenharia de SoftwareDO - 10.5753/opensciense.2021.17144, 2021)
Software development practices have evolved, and new approaches have emerged, like Global Software Development (GSD). In addition, software development companies started to adopt data-driven practices in parts of their business. However, using and sharing software process data in a distributed and heterogeneous environment, like the GSD context, could be a challenging topic for many software engineers. In this paper, we present a proposal for sharing software process provenance data using a model that extends PROV, the PROV- SwProcess model. An example of applying this model using a process from the industry that deals with error handling and the implementation of new features in an Enterprise Resource Planning system is presented and explains how the model allows sharing software process provenance data, in addition to providing inferences and insights about these data.